Synthesis and application of nanoporous carbon incorporated with cobalt ferrite composite and molecularly imprinted polymer for mercury removal from wastewater - Abubakar, Lawal (2023)
Water pollution has been a major challenge to environmental scientists today due to the release of toxic heavy metals from various industries. Among various heavy metals, mercury [Hg(II)] is considered as highly toxic due to its carcinogenicity and various health disorders. Different sources of Hg(II) pollution include effluents from mining, leather tanning and electroplating industries. Among various technologies, adsorptive removal of Hg(II) by using different adsorbents is more promising and economical. Among various adsorbents used, nanoporous carbon (NC) is well known for its high adsorption capacity due to large surface area and pore volume. In recent years, immense research has been focused towards converting the agricultural or lignocellulosic wastes into nanoporous carbon, since this technology not only solves the problem of waste disposal but also converts a potential waste into a valuable product that can be used as an adsorbent for effluent treatment. Palm kernel shell, a lignocellulosic material was selected as the precursor for the preparation of nanoporous carbon in the present investigation. Nanoporous carbons derived from Palm kernel shell (PKS) are materials with improved properties for applications in globally challenging areas in the world today such as water treatment, pollutant, pesticide, energy storage and batteries, catalysis and heavy metal adsorption. In this work, Palm kernel shell (PKS) was chemically activated with phosphoric acid (H3PO4) and the effect of temperature and impregnation ratio was investigated. At medium temperature (500 °C), impregnation ratio of 100% H3PO4, and carbonization time of 1 hour, nanoporous carbon with a surface area of 1280 m2 g-1 was achieved under ideal conditions. At various parameters, the surface structure, morphology, surface area, functional group, and thermal stability were investigated. This confirmatively showed that nanoporous carbon possessed a tremendous aptitude for various applications. Nanoporous carbon produced at 500 °C temperature (NC500) for 1 hr was most suitable for the adsorption of Hg(II) under the influences of pH, adsorbent dosage, initial concentration and contact time. The Freundlich model fit the adsorption isotherm best and was fitted with a pseudo-second order kinetic model. While it’s maximum Hg(II) adsorption capacity was 55.3 mg/g. The treatment of NC500 with molecularly imprinted polymer incorporated with nanoporous carbon (NC@MIP) and cobalt ferrite nanoparticle (NC@CoFe2O4 composite) were successfully synthesized, that brought an increase of carboxylic and amine groups on the surface of the NC500 that enhanced the adsorption of mercury. This was confirmed by the various characterizations such as XRD, FESEM, BET, FTIR, VSM and TGA. Batch adsorption was carried out at optimum experimental conditions of 0.3 g, 30 mg/L Hg(II), pH 4, 25 °C for NC500 and NC@MIP, and 0.3 g, 30 mg/L Hg(II), pH 3, 40 °C for NC@CoFe2O4 composite, demonstrating that Hg(II) removal was highly dependent on the adsorption parameters (dosage, contact time, solution pH, initial ion concentration and temperature). The treated nanoporous carbons had the highest mercury adsorption efficiency. The highest adsorption efficiency of NC@MIP for removing Hg(II) from aqueous solution at room temperature, pH 4 is 116 mg/g when the initial concentration of Hg(II) is 30 mg/L. Conversely, the synthesized nanomaterial NC@CoFe2O4 composite has saturation magnetization of 33.650 emu/g and obtained the maximum adsorption efficiency of 232.56 mg Hg(II)/g at a pH of 3, when the initial concentration of Hg(II) is 30 mg/L. The adsorption equilibrium data was well explained by Freundlich isotherm and isotherm parameters suggested that the adsorption of Hg(II) on the prepared NC@MIP and NC@CoFe2O4 composite is chemisorption adsorption. The adsorption of Hg(II) followed pseudo-second-order kinetic for the NC@MIP and NC@CoFe2O4 composite, while the thermodynamic parameters indicate that the enthalpy, entropy, and Gibbs free energy values show that the adsorption is compatible with spontaneous, favorable, and endothermic reactions. As a result, the synthesized composites can be used as an adsorbent with excellent performance in the field of mercury removal.